Role of reactive nitrogen species in male infertility - Doshi Sejal B; Khullar Karishma; Sharma Rakesh K; Agarwal Ashok (BMC, 2012)
Abstract Reactive nitrogen species (RNS) is a subset of free oxygen radicals called reactive oxygen species (ROS). Physiological levels of ROS are necessary to maintain the reproductive functions such as cell signaling, tight junction regulation, production of hormones, capacitation, acrosomal reaction, sperm motility, and zona pellucida binding. However, an excess of RNS can adversely affect reproductive potential by causing testicular dysfunction, decreased gonadotropin secretion, and abnormal semen parameters. Because such levels of RNS have been demonstrated in males with fertility problems and routine semen analysis has not been able to accurately predict IVF outcomes, it is imperative that novel strategies be developed in order to both assess and treat oxidative stress. This article describes both physiological and pathological roles of this unique subset of ROS.